Pengaruh Pemberian Reward And Punishment Terhadap Motivasi Belajar Bahasa Indonesia Siswa Kelas Tinggi Di Sekolah Dasar - Sindy Ashari (Jurnal Sultra Elementary School, 2024)
This study aims to examine the effect of reward and punishment on the learning motivation of high-grade students in elementary schools in learning Indonesian. This literature study refers to various relevant previous studies and theories of learning motivation. The results of the analysis show that giving rewards can increase students' intrinsic motivation, while punishment given wisely can help students understand the consequences of their actions. This study provides important implications for teachers in designing effective learning strategies.